Longitudinal shock of two elastic bars with one spherical end - An, Nguyen Thuc; To, Nguyen Dang; Son, Nguyen Hung (Vietnam Journal of Mechanics, 1993)
In [1] authors research problem of longitudinal shock of two elastic bars with one spherical end with the condition 0 < t < T2. In this paper authors continually researched this problem with the condition T2 < t < kT2 to finishing of the shock. According to the technology this problem is similar to the picture of driving piles.